AB0947 RECIPROCAL IMPACT OF FIBROMYALGIA ON DISEASE CHARACTERISTICS AND PHYSICAL AND PSYCOLOGICAL DOMAINS IN SJOGREN SYNDROME: CROSS SECTIONAL OBSERVATIONAL STUDY. (2nd June 2020) - Capacci, A.; Rubortone, P.; Varriano, V.; Paglionico, A.; Perniola, S.; Gigante, M. R.; Tolusso, B.; Alivernini, S.; Gremese, E.
Abstract : Background: Sjogren Syndrome (SS) is an autoimmune exocrinopathy, resulting mainly in ocular and oral dryness, with approximately half of patients displaying symptoms from different organ systems, further adding to the heterogeneous clinical phenotype of the disease. Fatigue and pain are common systemic symptoms in patients with primary SS and fibromyalgia is a frequent condition associated with chronic diseases. Objectives: The aim of the study was to evaluate the impact of concomitant fibromyalgia in patients with Sjogren Syndrome in terms of clinical features and disease activity. Methods: 50 patients with Sjogren Syndrome were enrolled in the study (100% female, age: 53.7 ± 13.2 years and disease duration: 8.7 ± 5.3 years), 25(50.0%) with concomitant fibromyalgia (SS/Fibro-group) and 25(50.0%) without (SS-group). 36 patients with primary fibromyalgia (Fibro-group) were included as control group. At study entry, demographic, educational, life-style and clinical parameters were recorded for each patient. SS was diagnosed according to the American College of Rheumatology (ACR) classification criteria (1) and fibromyalgia was diagnosed according to criteria for fibromyalgia defined by ACR (2). Moreover, each patient with fibromyalgia, with and without concomitant SS, was asked to fill a self-reported questionnaire to assess the impact of Fibromyalgia on multiple physical and psycological domains (Italian-FIQR). Results: Stratifying the study cohorts based on the demographic and life-style characteristics, no significant differences were found comparing SS-group, Fibro-group and SS/Fibro-group. However, considering the different organ involvement, SS/Fibro-group were more likely reporting arthralgia symptoms (100.0%) than SS-group (76.0% p=0.02), despite similar clinical evidence of arthritis-synovitis among the two groups (12.0% in both groups respectively, p=1.00). Moreover, SS/Fibro-group showed significantly lower ESSDAI score (2.8 ± 1.7) and higher ESSPRI score (7.0 ± 0.9) compared to SS-group (ESSDAI: 7.5 ± 3.7 p<0.001 and ESSPRI: 5.2 ± 1.4, p<0.001 respectively). Finally, analyzing the differential distribution of individual scores of physical and psycological domains of the Italian-FIQR Questionnaire, SS/Fibro-group did not differ compared to Fibro-group (p>0.05 for all the 21 questions included). Conclusion: SS is affected by concomitant fibromyalgia in terms of subjective-dependent parameters (i.e. joint complaints) however the concomitant SS does not affect the impact of fibromyalgia on physical and psycological domains, even if disease activity is higher in SS patients without fibromyalgia. References: [1]Shiboski SC et al. Arthritis Care Res, 2012 [2]Wolf F. et al. Arthritis Rheum 1990 Disclosure of Interests: Annunziata Capacci: None declared, Pietro Rubortone: None declared, Valentina Varriano: None declared, Annamaria Paglionico: None declared, Simone Perniola: None declared, Maria Rita Gigante: None declared, Barbara Tolusso: None declared, Stefano Alivernini: None declared, Elisa Gremese Speakers bureau: Abbvie, BMS, Celgene, Jannsen, Lilly, MSD, Novartis, Pfizer, Sandoz, UCB